1983
DOI: 10.1084/jem.158.1.246
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to normal human melanocytes in vitiligo.

Abstract: Most patients with active vitiligo (82% of 61) have antibodies to antigens of normal human melanocytes that can be detected by specific immunoprecipitation of radioiodinated, detergent-soluble, melanocyte macromolecules. Such antibodies were present in only 12% of patients with melanoma and in none of 35 patients with nonpigmentary skin diseases. The antibodies were directed to a common antigen(s) on melanocytes that was not present on normal fibroblasts or keratinocytes. These observations suggest that vitili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
1
3

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(112 citation statements)
references
References 8 publications
(13 reference statements)
1
107
1
3
Order By: Relevance
“…These examples include cases of spontaneous regression of primary and metastatic melanoma, and also the development of vitiligo in melanoma patients. These phenomena have been accompanied by various circulating anti-melanocyte antibodies and melanoma specific cytotoxicity conveyed by tumour infiltrating lymphocytes (Naughton et al, 1983;Bottger et al, 1992;Kawakami et al, 1994). Immunotherapy is most likely to eradicate metastatic disease when the tumour burden is minimal and when the host has not yet become immunosuppressed either by tumour itself (Akiyama et al, 1983), or by various chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…These examples include cases of spontaneous regression of primary and metastatic melanoma, and also the development of vitiligo in melanoma patients. These phenomena have been accompanied by various circulating anti-melanocyte antibodies and melanoma specific cytotoxicity conveyed by tumour infiltrating lymphocytes (Naughton et al, 1983;Bottger et al, 1992;Kawakami et al, 1994). Immunotherapy is most likely to eradicate metastatic disease when the tumour burden is minimal and when the host has not yet become immunosuppressed either by tumour itself (Akiyama et al, 1983), or by various chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…2 antibodies directed at melanoma, as well as cultured melanocytes (32)(33)(34). It is unclear what the incidence of antibodies to melanocytes or melanoma is among melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that vitiligo is, at least in part, caused by autoimmune responses mediated by cytotoxic T cells against melanocytes, causing depigmentation. In addition, many patients with vitiligo produce autoantibodies against proteins expressed in melanocytes (2)(3)(4). The lysis of human melanocytes by vitiligo patients' sera provides direct support for the autoimmune hypothesis of human vitiligo (5).…”
mentioning
confidence: 93%
“…Peptides (5 g) were spotted on the activated membranes and left to dry at room temperature. To block nonspecific binding sites, membranes were incubated for 1 h in PBS/0.05% (v/v) Tween 20 (PBST) containing 5% BSA and then with human polyclonal Ab (pAbs) 3 (250 g/10 ml incubation solution). Following 1 h incubation at room temperature (RT), membranes were washed for 10 min with PBST (3ϫ) and further incubated in PBST/5% BSA for 1 h with HRP-conjugated goat anti-human polyclonal Abs (1/10000) obtained from Sigma-Aldrich.…”
Section: Dot-blot Immunoassaymentioning
confidence: 99%